Association of Aortic Stiffness With Left Ventricular Remodeling and Reduced Left Ventricular Function Measured by Magnetic Resonance Imaging: The Multi-Ethnic Study of Atherosclerosis. (July 2016) - Ohyama, Yoshiaki; Ambale-Venkatesh, Bharath; Noda, Chikara; Chugh, Atul R.; Teixido-Tura, Gisela; Kim, Jang-Young; Donekal, Sirisha; Yoneyama, Kihei; Gjesdal, Ola; Redheuil, Alban; Liu, Chia-Ying; Nakamura, Tetsuya; et al.
Abstract : Background—: This study sought to assess cross-sectional associations of aortic stiffness assessed by magnetic resonance imaging with left ventricular (LV) remodeling and myocardial deformation in the Multi-Ethnic Study of Atherosclerosis (MESA). Methods and Results—: Aortic arch pulse wave velocity (PWV) was measured with phase contrast cine magnetic resonance imaging. LV circumferential strain (Ecc), torsion, and early diastolic strain rate were determined by tagged magnetic resonance imaging. Multivariable linear regression models were used to adjust for demographics and cardiovascular risk factors. Of 2093 participants, multivariable linear regression models demonstrated that higher arch PWV was associated with higher LV mass index ( B =0.53 per 1 SD increase for log-transformed PWV, P <0.05) and LV mass to volume ratio ( B =0.015, P <0.01), impaired LV ejection fraction (LVEF; B =−0.84; P <0.001), Ecc ( B =0.55; P <0.001), torsion ( B =−0.11; P <0.001), and early diastolic strain rate ( B =−0.003; P <0.05). In sex stratified analysis, higher arch PWV was associated with higher MVR ( B =0.02; P <0.05), impaired Ecc ( B =0.60; P <0.001), and LVEF ( B =−0.45; P <0.05), but with maintained torsion in women. Higher PWV was associated with impaired Ecc ( B =0.49; P <0.001) and LVEF ( B =−1.21; P <0.001), with lower torsion ( B =−0.17; P <0.001) in men. Conclusions—: Higher arch PWV is associated with LV remodeling, and reduced LV systolic and diastolic function in a large multiethnic population. Greater aortic arch stiffness is associated with concentric LV remodeling and relatively preserved LVEF with maintained torsion in women, whereas greater aortic arch stiffness is associated with greater LV dysfunction demonstrated as impaired Ecc, torsion, and LVEF, with less concentric LV remodeling in men. Abstract : Supplemental Digital Content is available in the text.